Pengujian Black Box pada Aplikasi Sistem Seleksi Sales Terbaik Menggunakan Teknik Equivalence Partitions - Fadhila Cahya Ningrum; Dandi Suherman; Sita Aryanti; Handika Angga Prasetya; Aries Saifudin (Jurnal Informatika Universitas Pamulang, 2019)
Testing on an application aims to check whether a program is running properly so that the program created will be a program that has good quality. The testing technique consists of Whitebox Testing and Blackbox Testing which are widely used by examiners is appropriate. Study the software that will be examined using Blackbox Testing is a best sales selection system consisting of 1 form that will be filled with sales data, as well as sales performance while in the company. The Best Sales Selection Application will be tested using Blackbox Testing where this test only aims to look the program is the same with the function desired by program without knowing the program code used. Types of testing of the various Blackbox methods one of which is the Equivalence Partitions used by the authors in this study. Equivalence Partitions technique is a test based on entering data on each form in the best sales selection system, each menu input will be tested and grouped according to function whether it is valid or invalid. So it is expected that with this test is the quality of the software produced in accordance with the expected function, and can provide benefits for the company.